"A Twenty-Hour-a-Day Job": The Impact of Frequent Low-Level Criminal Justice Involvement on Family Life. Issue 1 (May 2016) - Comfort, Megan
In the growing field of research on the consequences of criminal justice contact for family life, a heavy emphasis has been placed on how imprisonment influences the emotional, physical, and socioeconomic well-being of prisoners' loved ones. In this article, I elaborate on and analyze the experiences of family members of people with frequent, low-level criminal justice involvement. I draw on ethnographic data collected in partnership with a clinical social worker over the course of a three-year study of an intensive case management intervention for HIV-positive individuals. Findings indicate that loved ones' brief jail stays and community supervision through probation and parole pose hardships for family members that are distinct from those hardships that arise during imprisonment. These experiences are uniquely destabilizing, may confer specific risks to family members' well-being, and merit further study to inform programs, social services, and public policy.